2016
DOI: 10.1111/jsr.12388
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems and internet addiction among children and adolescents: a longitudinal study

Abstract: SUMMARYAlthough the literature has documented associations between sleep problems and internet addiction, the temporal direction of these relationships has not been established. The purpose of this study is to evaluate the bidirectional relationships between sleep problems and internet addiction among children and adolescents longitudinally. A fourwave longitudinal study was conducted with 1253 children and adolescents in grades 3, 5 and 8 from March 2013 to January 2014. The sleep problems of the student part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
157
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 29 publications
(45 reference statements)
7
157
0
9
Order By: Relevance
“…Sleep disturbances related to IA have been reported in previous studies in the adolescent and young adult groups [41, 43], either as a consequence of IA [4, 43] related to anxiety or mood problems, or as a predictor of IA [41], depicted as disturbed circadian rhythm [41]. However, these studies assessing sleep disturbance related to IA demonstrated overall sleep quality severity including total sleep duration except for specific problems of poor sleep [41, 43, 44].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Sleep disturbances related to IA have been reported in previous studies in the adolescent and young adult groups [41, 43], either as a consequence of IA [4, 43] related to anxiety or mood problems, or as a predictor of IA [41], depicted as disturbed circadian rhythm [41]. However, these studies assessing sleep disturbance related to IA demonstrated overall sleep quality severity including total sleep duration except for specific problems of poor sleep [41, 43, 44].…”
Section: Discussionmentioning
confidence: 75%
“…However, these studies assessing sleep disturbance related to IA demonstrated overall sleep quality severity including total sleep duration except for specific problems of poor sleep [41, 43, 44]. External factors such as exposure to the light source from the internet device, leading to suppression of melatonin secretion [45], and lack of physical activity that is important for restorative sleep [46] may help in explaining the results.…”
Section: Discussionmentioning
confidence: 99%
“…These students — who spend greater time in internet — are more likely to develop depressive symptoms [9]. On the other hand, internet addict students have higher chance of experiencing sleep problems [10]. These students — with sleep problems — are more likely to develop depressive symptoms [11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although the physical activity in adolescence brings innumerable health benefits, preventing diseases, obesity, insomnia, and stress 13,20,25 it seems to have little influence on extra facial pain and the presence of parafunctional habits. Since bruxism/clenching have a multifactorial origin [27][28][29][30][31] , they must be analyzed with caution because many factors can trigger the onset and not only the absence of physical activity. It is worth mentioning that bruxism, as well as parafunctions, generate peripheral sensitization and can lead to local acute pain resulting from the release of inflammatory substances in the muscle and joint tissue.…”
Section: Discussionmentioning
confidence: 99%